Improving Reading Skill by Using Buzz Group for Islamic Students in Islamic State Institute Pontianak - Vibry Andina Nurhidayah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2020)
The study reveal the reading improvement by using Buzz groups technique. This study used action research. This research finding that buzz groups technique can improve students’ reading comprehension. The improvement can be identified from students’ reading comprehension achievement in finding word meaning, finding detailed information, identifying the referent, identifying the main idea, identiying implied information, identifying the language characteristics of the text including identifying the generic structure of the text and identifying communicative purpose of text. The result score of pre-test is 60.2, the mean score of post-test 1 is 75.4, and the mean score of post-tes 2 is 83